Consumer Attitude Towards to Step-down Extension of Luxury Brand - Chen, Hsing-Yu (2010)
70% of revenue for luxury firms come from accessible luxury markets. In order to make luxury brands to be more accessible to wider public clients, many luxury-brand companies apply brand extension to expand to accessible luxury markets. Step-down brand extension is an approach that can minimise damages cause by brand extension, because it can keep attributes of core luxury brands, such as superior quality, design-led and strong emotional engagement. Hence it is curtail to understand the relationship between consumer attitude and step-down extension of luxury brands. In this research, different purchasing motives for step-down luxury brands and core brands will be examined and consumer attitude towards to both step-down luxury brand and core luxury brands will be investigated.